2015
DOI: 10.3109/00498254.2015.1036954
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive assay for nine major cytochrome P450 enzymes activities with 16 probe reactions on human liver microsomes by a single LC/MS/MS run to support reliablein vitroinhibitory drug–drug interaction evaluation

Abstract: 1. A comprehensive method for the simultaneous characterization of xenobiotic compound inhibition of nine major CYP enzymes in human liver microsomes was established by using 16 CYP-catalyzed reactions of 14 probe substrates with three cocktail incubation sets and a single LC/MS/MS analysis. 2. The three cocktail subgroups were developed to minimize the effects of organic solvents, polyunsaturated fatty acids and mutual substrate interactions: Group I was composed of tolbutamide (CYP2C9), S-mephenytoin (CYP2C1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 67 publications
1
32
0
Order By: Relevance
“…In this study, the same internal standard was used for the two cocktail sets although it is ideal to use different internal standards for two separate cocktail sets. Several studies also successfully used the same internal standard for cocktail sets (Kim et al, ; Lee & Kim, ; Peng et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the same internal standard was used for the two cocktail sets although it is ideal to use different internal standards for two separate cocktail sets. Several studies also successfully used the same internal standard for cocktail sets (Kim et al, ; Lee & Kim, ; Peng et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro P450 enzyme inhibition assays have been used routinely to assess the P450‐mediated DDI potential of these nine enzymes. Several cocktail assays (also known as N‐in‐one assays) that use a mixture of P450 probe substrates added to liver microsomal incubation (Peng et al, ) have been developed for the high‐throughput screening (HTS) of the P450 inhibition of the nine major human P450 isoforms simultaneously using liquid chromatography–tandem mass spectrometry (LC–MS/MS) (Dinger et al, ; Kim et al, , ; Li, Huang, Nikolic, & van Breemen, ; Sevior et al, ; Tolonen, Petsalo, Turpeinen, Uusitalo, & Pelkonen, ). Several earlier reported cocktail approaches used the N‐in‐one assay (Abass & Pelkonen, ; Dahlinger et al, ; Kozakai et al, ; Li et al, ; Liu et al, ; Sevior et al, ; Tolonen et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that in the EROD assay, the S9 supplement might have an additional direct inhibitory effect on the resorufin fluorescence, and should be used with caution in this approach [50]. Like in the EROD assay, cytochrome activity can be measured using other fluorescent substrates, and specific assays are available for different enzyme subfamilies and polypeptides (CYP1A2, CYP2C19, CYP2C9, CYP2D6, CYP3A4) [51,52]. Moreover, liquid-chromatography/mass-spectroscopy (LC-MS/MS) can be used to detect and quantify specific cytochrome/substrate reactions (CYP2B6/bupropion, CYP2C8/paclitaxel, CYP2C9/tolbutamide, CYP2C19/Smephenytoin, CYP2D6/dextromethorphan, CYP3A4/ midazolam, CYP3A4/testosterone) [53].…”
Section: Viability: Metabolismmentioning
confidence: 99%
“…38 The quality and quantity of Measurements of cYP 1a2, 2c11, and 3a2 activity CYP450 1A2, CYP450 2C11, and CYP450 3A2 activity were assessed as described. [39][40][41] All microsomal incubations were conducted for 60 minutes at 37°C in a final volume of 500 μL. Each incubation mixture contained pooled microsomes (1.0 mg protein/mL) and an nicotinamide adenine dinucleotide phosphate-regenerating system consisting of MgCl 2 (10 mM), glucose 6-phosphate (10 mM), NADP + (1.0 mM), and 6-phosphate dehydrogenase (2.0 U/mL).…”
Section: Measurements Of Cytokines and Antioxidant Abilitymentioning
confidence: 99%